Antigua and Barbuda : Detailed Assessment of Compliance with Basel Core Principles for Effective Banking Supervision-Offshore Banking. (IMF Staff Country Reports; Country Report ;, 2004)
The Detailed Assessment of Antigua and Barbuda's compliance with the Basel Core Principles for Effective Banking Supervision is presented. The largest bank represents 61 percent of the sector's aggregated assets, highlighting an important degree of concentration. Investment portfolios represent the bulk of banks' assets, and are predominantly composed of government and corporate bonds and equities. Loan portfolios include a number of large exposures, some exceeding 25 percent of capital, and/or connected party loans.